2014
DOI: 10.3346/jkms.2014.29.8.1094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multimodality Approach for Patients with Leptomeningeal Metastases from Solid Tumors

Abstract: The purpose of this study was to evaluate treatment patterns, outcome and prognosticators for patients with leptomeningeal metastases from solid tumor. Medical records of 80 patients from January 1, 2004 to May 31, 2011 were retrospectively reviewed. Most frequent site of origin was the lung (59%) followed by the breast (25%). Most patients were treated with intrathecal chemotherapy (90%) and/or whole brain radiotherapy (67.5%). Systemic therapy was offered to 27 patients (33.8%). Percentage of patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Although the recent advances in systemic treatment of advanced cancers have resulted in significant improvements in survival, the prognosis of patients with LM remains poor. In this study, the median survival was only 2.4 months (95% CI, 1.0–3.7) in 58 patients with sold tumor who were diagnosed with LM, which is similar to previous reports of LM in patients with solid tumors (1.5 to 4.4 months) [ 6 11 12 ]. A good PS, systemic chemotherapy after LM diagnosis, and a prior history of brain radiation were associated good survival in our patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the recent advances in systemic treatment of advanced cancers have resulted in significant improvements in survival, the prognosis of patients with LM remains poor. In this study, the median survival was only 2.4 months (95% CI, 1.0–3.7) in 58 patients with sold tumor who were diagnosed with LM, which is similar to previous reports of LM in patients with solid tumors (1.5 to 4.4 months) [ 6 11 12 ]. A good PS, systemic chemotherapy after LM diagnosis, and a prior history of brain radiation were associated good survival in our patients.…”
Section: Discussionsupporting
confidence: 90%
“…However, in studies on LM from Asian countries, melanomas were rare, and gastric cancer was one of the most common origins of LM in Asia including Korea. [ 6 11 12 ]. In this study, consistent with these Asian reports, breast cancer (39.7%), lung cancer (including NSCLC and small cell lung cancer, 22.4%), and gastric cancer (25.9%) were common causes of LM, and melanoma was reported in only one case.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that although systemic chemotherapy drugs have limited ability to penetrate the blood-brain barrier, the concentration of drugs that can reach the cerebrospinal uid is very low, systemic treatment is thereby not an effective method for the treatment of NM, it is still an independent factor affecting the prognosis of NM patients. Multiple retrospective analyses have shown that systemic chemotherapy can prolong the survival time of patients [29][30][31][32] , and can simultaneously treat active systemic tumors and meningeal lesions. Targeted therapy is a brand-new treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…Although nearly every advanced solid tumor has been reported to metastasize to leptomeninges, LM is frequently detected in lung cancer, breast cancer, and melanoma [3] [6]. However, in studies on LM from Asian countries, cases arising from melanoma were rare, and gastric cancer was one of the most principal etiologies of LM [7][8] [9]. However, LM is not a common complication of gastric cancer, the prevalence of LM was reported 0.17-0.43% [10] [19].…”
Section: Discussionmentioning
confidence: 99%
“…[9][25]. Most patients have extensive systemic tumor burden at time of LM diagnosis, and systemic chemotherapy could be effective for treatment of systemic disease.Several studies reported that PS was one of the most important prognostic factors in patients with LM [7][8][16][25].…”
mentioning
confidence: 99%